Intraoperative angiography with indocyanine green injection for precise localization and resection of small bowel bleeding. Issue 1 (13th August 2020) - Kawachi, Jun; Ogino, Hidemitsu; Shimoyama, Rai; Ichita, Chikamasa; Isogai, Naoko; Murata, Takaaki; Miyake, Katsunori; Nishida, Tomoki; Fukai, Ryuta; Kashiwagi, Hiroyuki
Abstract : Aim: Bleeding in the small bowel rarely occurs, and its treatment is challenging. Surgery is sometimes required in unstable patients; however, intraoperative identification of the bleeding site is extremely difficult. Many methods have been reported, but no standard strategy has been established yet. Here, we aimed to assess the safety and feasibility of intraoperative angiography with indocyanine green staining to accurately identify small bowel bleeding sites. Methods: This retrospective study analyzed contrast‐enhanced computed tomography images of patients ( n = 8) with small bowel extravasation who underwent surgery. If extravasation or other vessel abnormalities that were potential bleeding sites were detected on intraoperative angiography, a microcatheter was placed as close as possible to the extravasation site. Laparotomy was carried out, and 3–5 mL indocyanine green was injected through the microcatheter. The green‐stained segment of the small bowel was resected. Results: Seven of the eight patients had positive angiographic findings and underwent bowel resection. The eighth patient had no abnormalities and hence did not undergo laparotomy. The rate of hemostatic success among the resected cases was 85.7% (six of seven cases). The resected specimens showed pathologic features in six of the seven patients (85.7%), all of whom achieved hemostasis. One patient had pneumonia and congestive heart failure that required longer hospital stay, but no mortality occurred. Conclusions: Intraoperative angiography with indocyanine green injection, followed by resection for massive small bowel bleeding is effective. This can be a therapeutic option for hemodynamically unstable patients. Abstract : Localization of the small bowel bleeding site with intraoperative angiography and indocyanine green injection.